2014
DOI: 10.9790/2402-08135966
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Biological Study on The Effect of Flaxseed on Rats Suffer from Nephropathy.

Abstract: The present study was conducted to investigate the effect supplemented diets with different doses of flaxseed on some biological, biochemical and histopathology changes in rats suffering from nephropathy. Thirty adult male albino rats "Sprague were divided into two main groups, the first main group fed on basal diet as a (negative control group). The second main group (24 rats) injection with 10 ml glycerol /kg dissolve in saline solution (glycerol / saline solution v/v) to induce renal failure, the dose of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Wahba and Ibrahim 45 reported that the administration of flaxseed oil produced significant decreases in the elevated BUN and UA when compared with the positive control group. El-Sayed et al, 46 stated that the renal failure rats fed on a diet containing 5% and 7% flaxseed get better in body weight gain% and kidney functions.…”
Section: Discussionmentioning
confidence: 99%
“…Wahba and Ibrahim 45 reported that the administration of flaxseed oil produced significant decreases in the elevated BUN and UA when compared with the positive control group. El-Sayed et al, 46 stated that the renal failure rats fed on a diet containing 5% and 7% flaxseed get better in body weight gain% and kidney functions.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14] As a powerful antioxidant, flaxseed has a role in protecting the liver and kidneys from strong oxidants, 15 and prevent oxidative stress-induced diseases such as renal failure, liver failure, hyperlipidemia, and diabetes. 16 Monosodium glutamate (MSG) was used in Japan as a flavour enhancer in many types of food, producing a flavour called umami meaning savory. 17,18 It is also used in disguised forms, such as in flavoured natural flavours, yeast extract, hydrogenated protein, and in soy protein.…”
mentioning
confidence: 99%
“…[11][12][13][14] As a powerful antioxidant, flaxseed has a role in protecting the liver and kidneys from strong oxidants, 15 and prevent oxidative stress-induced diseases such as renal failure, liver failure, hyperlipidemia, and diabetes. 16 Monosodium glutamate (MSG) was used in Japan as a flavour enhancer in many types of food, producing a flavour called umami meaning savory. 17,18 It is also used in disguised forms, such as in flavoured natural flavours, yeast extract, hydrogenated protein, and in soy protein.…”
mentioning
confidence: 99%